Meningkatkan Hasil Belajar Siswa Dalam Mata Pelajaran Ilmu Pengetahuan Alam Materi Penggolongan Hewan Berdasarkan Jenis Makanannya Dengan Menggunakan Media Audio Visual Bagi Siswa Kelas Iv Sd Negeri Sukamanah 2 - Ratu Fani Andriania; Ratna Dewi; Rifki Arif Nugraha; Ajeng Mulia Sari (Desanta Publisher, 2023)
The method used in this research is collaborative classroom action research (PTK). Researchers collaborate with teachers to plan, identify, observe and implement the actions that have been designed. The research design used is a spiral system classroom action research using the Hopkins and John Eliot model which begins with preliminary action then continues with planning, action, observation and reflection. The research was carried out in 2 cycles. The research was carried out at SDN Sukamanah 2, Kaduhejo District, Pandeglang Regency. The samples selected in this research were 22 grade 4 students, consisting of 14 boys and 8 girls. In this research, there were several stages carried out from pre-cycle research, cycle I, and cycle II The results of this research show that in pre-cycle conditions, 1200 students completed their studies, around 18.18% of 22 students with an average class of 55. After carrying out activities in cycle I, the number of students who completed their studies became 1470 students from 22 students. or around 50% with an average score of 67. In cycle II, it was discovered that there were 22 students out of 20 students who had successfully completed their studies, obtaining an average score of 85 with a completion percentage of 90.90% and could be said to be successful. The increase in student learning outcomes in Natural Sciences subjects, the material on classifying animals based on the type of food, is motivated by the use of effective and fun learning media so that it can motivate students' interest in learning to be even better. The learning media used is audio-visual media.